PENGATURAN PENERBANGAN SIPIL INTERNASIONAL MENURUT HUKUM INTERNASIONAL YANG MELINTASI ANTAR NEGARA - Sudirman H. Nainggolan; Sutiarnoto Sutiarnoto; Chairul Bariah (Journal of USU International Law, 2014)
ABSTRACT SETTING THE INTERNATIONAL CIVIL AVIATION ACCORDING TO INTERNATIONAL LAW ACROSS THE INTER-STATE Civil aviation organization of international and national should refer to the norms of international and national laws that apply, to ensure the safety of passengers, crew aircraft, aircraft or goods transported. Where the implementation of civil aviation are arranged in a variety of international conventions The problem in this study is How open sky policy as air law instruments. How will the international law on state sovereignty over its territory and space in the international civil aviation settings How international law that crosses between States. This type of research used in this study is a normative legal research. Normative legal research is a research method that refers to the legal norms contained in laws and court decisions. Open sky policy as air law instruments. Open Sky Policy is an Open Skies agreement which allows air freight to make decisions in air travel capacity, pricing, and fully make liberal in the conditions of flight activity. Open sky policy (OSP) can be bilateral or multilateral. Setting international law on state sovereignty over space in the region is Article 1 of the 1944 Chicago Convention on international civil aviation, which reads: The contracting states recognize that every state complete and exclusive sovereignty over the airspace above its territory (each State bound by the Convention guarantees existing sovereign air space above its territory fully and exclusively). The setting of international civil aviation under international law that crosses between the State is Article 2 of the 1944 Chicago Convention over again explained that for the purposes of the 1944 Chicago Convention is meant State border (state territory) Keywords: Setting the International Civil Aviation